2022
DOI: 10.1126/sciadv.abo3991
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific epigenetic development in the mouse hypothalamic arcuate nucleus pinpoints human genomic regions associated with body mass index

Abstract: Recent genome-wide association studies corroborate classical research on developmental programming indicating that obesity is primarily a neurodevelopmental disease strongly influenced by nutrition during critical ontogenic windows. Epigenetic mechanisms regulate neurodevelopment; however, little is known about their role in establishing and maintaining the brain’s energy balance circuitry. We generated neuron and glia methylomes and transcriptomes from male and female mouse hypothalamic arcuate nucleus, a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…We observed sex-specific POMC methylation, supporting a previous finding in mouse hypothalamic arcuate nucleus and disease-related epigenome-wide association studies, for example, for Alzheimer’s disease ( 44 46 ). The molecular cause for this sexual dimorphism remains elusive and needs to be addressed in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…We observed sex-specific POMC methylation, supporting a previous finding in mouse hypothalamic arcuate nucleus and disease-related epigenome-wide association studies, for example, for Alzheimer’s disease ( 44 46 ). The molecular cause for this sexual dimorphism remains elusive and needs to be addressed in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, MacKay et al . showed a differential methylation pattern of specific genes expressed in neurons of the ARH across postnatal development (P12-P35), including Glp1r and Cck in male mice, and Gipr and Cck in females, strengthening the role of these gut peptides on the hypothalamic development in a sex-specific manner [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of both methylating and demethylating enzymes in the hypothalamus is developmentally regulated and shows different activity patterns between male and female brains (29). Most recently, MacKay et al have shown that post-natal epigenetic maturation in the ARC is cell type and sex specific and occurs particularly in genomic regions enriched for heritability of BMI in humans (30).…”
Section: Epigenetic Regulation Of Neural Maturationmentioning
confidence: 99%
“…Most recently, MacKay et al. have shown that post-natal epigenetic maturation in the ARC is cell type and sex specific and occurs particularly in genomic regions enriched for heritability of BMI in humans ( 30 ).…”
Section: Development Of Hypothalamic Energy Balance Circuitsmentioning
confidence: 99%